Amentoflavone and Kaempferol Glycosides from the Aerial Parts of Cissampelos pareira - Devkota, Hari Prasad; Miyazaki, Sena; Yahara, Shoji (Nepal Journal of Biotechnology, 2017)
Aerial parts of Cissampelos pareira L. (Family: Menispermaceae), commonly known as “Batulpate” in Nepal, are used for the treatment of fever, indigestion and to stop bleeding after child birth. In this study, a biflavonoid, amentoflavone; and two kaempferol glycosides, kaempferol 3-O-b-D-glucopyranoside and kaempferol 3-O-b-D-glucuronopyranoside were isolated from 70% MeOH extract of the aerial parts. Structures of these compounds were elucidated on the basis of 1H- and 13C-NMR spectral data. To the best of our knowledge, it is the first report on the isolation of these compounds from a plant belonging to family Menispermaceae.Nepal Journal of Biotechnology. Dec. 2017 Vol. 5, No. 1:1-4